A preliminary study on how hypohydration affects pain perception. (20th January 2016) - Bear, Tracey; Philipp, Michael; Hill, Stephen; Mündel, Toby
Abstract: Chronic pain is a prevalent health issue with one in five people suffering from some form of chronic pain, with loss of productivity and medical costs of chronic pain considerable. However, the treatment of pain can be difficult, as pain perception is complex and can be affected by factors other than tissue damage. This study investigated the effect of hypohydration (mild, voluntary dehydration from ∼24 h of limiting fluid intake, mimicking someone drinking less than usual) on a person's pain perception. Seventeen healthy males (age 27 ± 5 years) visited the laboratory on three occasions, once as a familiarization and then twice again while either euhydrated (urine specific gravity: 1.008 ± 0.005) or hypohydrated (urine specific gravity: 1.024 ± 0.003, and −1.4 ± 0.9% body mass). Each visit, they performed a cold pressor test, where their feet were placed in cold water (0–3°C) for a maximum of 4 min. Measures of hydration status, pain sensitivity, pain threshold, and catastrophization were taken. We found that hypohydration predicted increased pain sensitivity (β = 0.43), trait pain catastrophizing, and baseline pain sensitivity (β = 0.37 and 0.47, respectively). These results are consistent with previous research, and suggest that a person's hydration status may be an important factor in their perception of acute pain.